Gram‐Scale Bottom‐Up Synthesis of Macrographene. Issue 41 (4th November 2019) - Prakash, Sadasivan P.; Daisymol, Kurisingal B.; Gopidas, Karical R.
Abstract: Herein we report a very facile, bottom‐up synthesis of macrographene sheets of up to 1–2 μm size, in two steps from readily available starting materials under mild reaction conditions. The synthesis involved the reduction of 4, 4'‐biphenylene bisdiazonium salt in aqueous solution at room temperature using methanolic sodium borohydride. The reduction reaction results in the formation of 4, 4'‐biphenylele biradicals which underwent rapid addition reactions to give a cross‐linked polycyclic aromatic hydrocarbon frame work. Scholl oxidation of the aromatic frame work gave macrographene sheets in good yields in gram quantities. Formation of the graphene sheets was confirmed by several technique including X‐ray photoelectron spectroscopy, Raman spectroscopy, TEM and AFM analysis. Abstract : Reduction of 4, 4'‐biphenylene bisdiazonium tetrafluoroborate in aqueous medium using sodium borohydride generated the highly reactive 4, 4'‐biphenylele biradicals which underwent radical addition and radical‐radical coupling to give a polymeric organic network. This material when subjected to Scholl cyclodehydrogenation gave macrographene sheets of up to 2 μm size in good yield. The graphene material was characterized by several techniques including X‐ray photoelectron spectroscopy, Raman spectroscopy, TEM and AFM.